Aurora-A Kinase as a Promising Therapeutic Target in Cancer - D’Assoro, Antonino B.; Haddad, Tufia; Galanis, Evanthia (Frontiers in Oncology, 2016)
Mammalian Aurora family of serine/threonine kinases are master regulators of mitotic progression and are frequently overexpressed in human cancers. Among the three members of the Aurora kinase family (Aurora-A, -B and –C), Aurora-A and Aurora-B are expressed at detectable levels in somatic cells undergoing mitotic cell division. Aberrant Aurora-A kinase activity has been implicated in oncogenic transformation through the development of chromosomal instability (CIN) and tumor cell heterogeneity. Recent studies also reveal a novel non-mitotic role of Aurora-A activity in promoting tumor progression through activation of epithelial mesenchymal transition (EMT) reprogramming resulting in the genesis of tumor initiating cells. Therefore, Aurora-A kinase represents an attractive target for cancer therapeutics, and the development of small molecule inhibitors of Aurora-A oncogenic activity may improve the clinical outcomes of cancer patients. In the present review, we will discuss mitotic and non-mitotic functions of Aurora-A activity in oncogenic transformation and tumor progression. We will also review the current clinical studies evaluating small molecule inhibitors of Aurora-A activity and their efficacy in the management of cancer patients.